2012
DOI: 10.1111/j.1439-0531.2012.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ozone and Other Treatment Modalities for Retained Placenta in Dairy Cows

Abstract: Contents Retained placenta is a worldwide recognized clinical condition in puerperal cows, which can significantly affect their health and fertility. Available treatment modalities are often of questionable efficacy or associated with time constraints, practicality or monetary considerations for their wide application in a routine dairy practice. The objective of this study was to compare and assess the efficacy of different treatment options, including a novel ozone treatment, for the retained placenta. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
0
15
0
4
Order By: Relevance
“…Due to the well-recognized detrimental effects of antibiotic use, it is urgent to find a safe and effective alternative to antibiotic therapy for the treatment of RFM in ruminants. With the use of ozone between 12-24 hours (or even 36 hours) after birth, the duration of days open is comparable to those recorded in cows with physiological puerperium (DJURICIC et al, 2012a;ZOBEL and TKALCIC, 2013).…”
Section: Use Of Ozone Preparations In Ruminantsmentioning
confidence: 50%
See 3 more Smart Citations
“…Due to the well-recognized detrimental effects of antibiotic use, it is urgent to find a safe and effective alternative to antibiotic therapy for the treatment of RFM in ruminants. With the use of ozone between 12-24 hours (or even 36 hours) after birth, the duration of days open is comparable to those recorded in cows with physiological puerperium (DJURICIC et al, 2012a;ZOBEL and TKALCIC, 2013).…”
Section: Use Of Ozone Preparations In Ruminantsmentioning
confidence: 50%
“…DJURICIC et al (2012a), ZOBEL and TKALCIC (2013), DJURICIC et al (2015) and ĐURIČIĆ et al (2016) reported the positive effects of ozone treatment of RFM in cows, goats and ewes, as well as of clinical metritis/ endometritis/ in cows and ewes (ĐURIČIĆ et al, 2014;ZOBEL et al, 2014;ĐURIČIĆ et al, 2016). These effects were evident due to the fact that an ozone preparation applied to the uterus resulted in significantly better recovery in relation to the other preparations registered (antibiotics) for treatment of such conditions.…”
Section: Use Of Ozone Preparations In Ruminantsmentioning
confidence: 85%
See 2 more Smart Citations
“…A definição de retenção de placenta é baseada no processo fisiológico de expulsão da membrana fetal do útero de vaca (Zobel & Tkalčić 2013) e se caracteriza como a falha da expulsão da placenta dentro de 12 a 24 horas após o parto (Kelton et al 1998, Fourichon et al 1999, representando condição patológica (Zobel & Tkalčić 2013). A liberação da placenta envolve a perda da adesão materno-fetal e ocorre somente após a maturação do placentoma, sendo que as contrações uterinas ajudam mecanicamente essa liberação que ocorre fisiologicamente entre três e seis horas após o parto (Meça et al 2006).…”
Section: Introductionunclassified